Bioinformatics and expression analyses of heat shock protein 90 gene family in Rhododendron ovatum - LI Fengyan; QU Fangqian; ZHAO Fangmeng; WANG Qi; ZHOU Hong; ZHANG Liangsheng; XIA Yiping; WANG Xiuyun (浙江大学学报. 农业与生命科学版, 2023)
To explore the roles of heat shock protein 90 (Hsp90) in plant growth development and response to high temperature stress, this study identified the Hsp90 family through bioinformatics methods in the whole genome of Rhododendron ovatum, which is a highly ornamental and widely adaptive species of Rhododendron. Gene structure, cis-acting elements, evolution, and expression pattern of the Hsp90 family were subsequently analyzed. The results showed that 11 members of the Hsp90 family were identified in R. ovatum, which were located on five chromosomes. Cis-acting element analysis showed that all the 11 members of the Hsp90 family were involved in the processes of plant hormone metabolism and stress responses. The phylogenetic tree of Hsp90 family in Arabidopsis thaliana, Solanum lycopersicum, Camellia sinensis, R. simsii, R. delavayi, R. henanense, and R. ovatum was constructed, within four main clades. Evolutionary analysis showed that the Hsp90 family has undergone purification selection during the differentiation of Rhododendron species. Moreover, the expression patterns of Hsp90 family in different tissues and under high temperature treatments indicated that Hsp90 family plays roles in flower development and the response of plants to high temperature stress. This study provides a foundation for further study of the functions of Hsp90 genes in Rhododendron.